PERILAKU MAKAN SIAMANG DEWASA (Hylobates syndactylus Raffles, 1821) YANG HIDUP DI HUTAN TERGANGGU DAN TIDAK TERGANGGU - Abdul Rosyid (Universitas Tadulako, 2007)
The feeding behavior and of hylobates syndactylus (siamang) was investigated at the Way-Canguk Research area inBukit-Barisan Selatan National Park between the months of February and July 2002. The research was conducted in undisturbedforest area (F1) and disturbed forest area (F2). Focal animal sampling method was use with and interval of 5 minutes. Sixsiamangs in each forest types were observed. The results of the investigations concluded that F1 and F2 siamangs spend moretime resting than feeding. The percentage of feeding activity whichy is done by F1 and F2 Siamangs are 31% and 34%. Theactivity began at 6 until 7 am and increased to midday until 2 pm. After that, the activity decreased until 5.30 pm. The monthlyrange correlates negatively activity of F1 and F2 siamangs use mostly the middle layer of the canopy.Keywords : The feeding activites, Hylobates syndactylus, Bukit -Barisan Selatan National Park, disturbed, undisturbed.